Condensed ring compound for organic electroluminescent device
By developing xanthode derivative materials with high thermal stability and excellent front-line orbital energy levels, the bottleneck of blue light OLED devices has been solved, and the luminous efficiency and life are significantly improved. It is suitable for OLED light emitting devices and display devices.
Patent Information
- Application Number
- CN202411297425.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
AI Technical Summary
The performance improvement of blue light OLED devices is limited by the performance bottleneck of blue light emitting materials, especially the wide energy gap and low luminous efficiency, which makes it difficult to compare with green and red light devices in terms of efficiency and life.
Develop a fused ring compound based on xanthan derivatives to build a material with high thermal stability and excellent front-line orbital energy level through specific groups and sites modifications, as a main material or a luminescent material to improve OLED devices efficiency, lifespan and color purity.
Through the application of xanthode derivatives, the luminous efficiency and service life of OLED devices are significantly improved, and the color purity is improved. It is suitable for OLED light emitting devices and display devices, achieving performance matching with green and red light devices.
Smart Images

Figure CN119219657A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic light-emitting materials and relates to a condensed ring compound used for an organic electroluminescent device. Background Art
[0002] The basic structure of OLED elements is complex and delicate, usually composed of multiple layers of organic thin films and electrodes, including anode, hole injection layer, hole transport layer, electron blocking layer, light-emitting layer, hole blocking layer, electron transport layer, electron injection layer and cathode. The design of this multi-layer structure aims to optimize the injection, transport and recombination process of carriers, so as to achieve efficient and stable light emission. Under the action of an external electric field, holes are injected from the anode and electrons are injected from the cathode. The two meet and recombine in the light-emitting layer to form excitons. When the excitons return to the ground state through radiation transition, they release energy and emit visible light in the form of photons. This process is the basic principle of OLED light emission. In the industrialization process of OLED technology, green and red OLED devices have made significant progress, mainly due to the successful application of phosphorescent materials. Phosphorescent materials have significantly improved the performance of green and red OLED devices with their efficient energy conversion ability and long luminescence life, and promoted their widespread application in high-end display products. However, in comparison, the development of blue OLED devices is relatively lagging, mainly subject to the performance bottleneck of blue light emitting materials. The key to improving the performance of blue OLED devices lies in the development of high-quality blue luminescent materials and matching host materials. Due to the inherent characteristics of blue luminescent materials, such as wider energy gap and lower luminous efficiency, blue OLED devices are difficult to compete with green and red devices in terms of efficiency and life. In order to overcome this problem, researchers are committed to developing more blue luminescent materials and doping them in suitable host materials to reduce the exciton quenching effect and improve the energy transfer efficiency, thereby improving the luminescent performance of the device. Therefore, how to develop blue luminescent materials with both high luminous efficiency and good stability, as well as matching high-efficiency host materials, has become a hot and difficult issue in the current OLED technology field. Summary of the invention
[0003] In order to overcome the above technical problems, the present invention has developed a condensed ring compound for organic electroluminescent devices. Based on the unique molecular rigid structure of xanthene condensed ring derivatives, the present invention has high thermal stability. After modification with appropriate groups and specific sites, the constructed material can obtain a better frontier orbital energy level and a higher fluorescence quantum yield. As a main material and a luminescent material, it can improve the device efficiency, life, color purity and other performances, and is expected to be industrialized.
[0004] In one aspect, the present invention relates to a class of xanthene derivative compounds having a structure as shown in formula (I):
[0005]
[0006] Among them, X 1 or X 2 Any one selected from O, S or CR 1 R 2 , and the other is a single bond;
[0007] L is selected from fused ring aromatic groups, amino derivatives, and heteroaromatic groups containing nitrogen, oxygen, sulfur, and boron atoms;
[0008] Ar 1 is selected from substituted or unsubstituted aryl groups having 6 to 30 carbon atoms;
[0009] R 1 , R 2 is methyl or phenyl;
[0010] At least 0 hydrogen atoms are replaced by deuterium atoms.
[0011] Further preferably, in the compounds provided by the present invention, in said L, said condensed ring aromatic group is selected from phenyl, naphthyl, anthracenyl, pyrenyl, phenanthrenyl, benzanthryl, Base and other groups.
[0012] Further preferably, in the compound provided by the present invention, in the L, the heteroaryl group is selected from a substituted or unsubstituted furyl group, a substituted or unsubstituted carbazolyl group, and a substituted or unsubstituted thienyl group.
[0013] Furthermore, in the compounds provided by the present invention, X 1 or X 2 Any one of A1 to A6 is O, and the compound has a structure shown in any one of A1 to A6,
[0014]
[0015] Furthermore, in the compounds provided by the present invention, X 1 or X 2 Any one of which is S, the compound has a structure shown in any one of B1 to B6,
[0016]
[0017] Furthermore, in the compounds provided by the present invention, X 1 or X 2 Any one is CR 1 R 2 , the compound has a structure shown in any one of C1 to C6,
[0018]
[0019] Illustratively, in the compound provided by the present invention, the compound has the chemical structure shown in any one of compounds 1 to 209,
[0020] When X 1 or X 2 When any one of them is O, the structures are compound 1-compound 54, compound 115-compound 129, compound 140-compound 144, compound 155-compound 159, compound 170-compound 174, compound 185-compound 189, compound 213-compound 214, compound 218-compound 219;
[0021] When X 1 or X 2 When any one of them is S, the structures are Compound 55-Compound 79, Compound 110-Compound 114, Compound 130-Compound 134, Compound 145-Compound 149, Compound 160-Compound 164, Compound 175-Compound 179, Compound 190-Compound 194;
[0022] When X 1 or X 2 Any one of them is CR 1 R 2 When, the structures are compound 80-compound 109, compound 135-compound 139, compound 150-compound 154, compound 165-compound 169, compound 180-compound 184, compound 195-compound 212, compound 215-compound 217;
[0023]
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033] Here, D indicates that a hydrogen atom is replaced by deuterium.
[0034] In another aspect, the present invention relates to an organic electroluminescent device comprising a light-emitting layer, wherein the light-emitting layer comprises the compound.
[0035] Furthermore, in the organic electroluminescent device provided by the present invention, the compound is used as a host material or a light-emitting material.
[0036] In another aspect, the present invention relates to the use of the compound in an organic electroluminescent device.
[0037] In another aspect, the present invention relates to an organic electroluminescent display device, comprising the organic electroluminescent device.
[0038] In another aspect, the present invention relates to application of the organic electroluminescent device in an organic electroluminescent display device.
[0039] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0040] The present invention constructs a structure with certain molecular distortion by combining xanthene furan, xanthene thiophene, and xanthene fluorene with condensed ring aromatic groups or amino groups and heteroaromatic groups containing N, O, and S at specific positions, and further constructs a series of deuterated or non-deuterated compounds through modification with specific types of substituents, thereby improving the efficiency, lifespan, and other properties of organic electroluminescent materials. The compounds provided by the present invention can be used as the main material of the light-emitting layer or the light-emitting material, and can significantly improve the performance of the light-emitting device, achieve high efficiency, long life, and excellent color purity, and are widely applicable to OLED light-emitting devices and display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 Schematic diagram of the structure of an organic electroluminescent element.
[0043] Among them, 1 is the substrate, 2 is the anode layer, 3 is the hole injection layer, 4 is the first hole transport layer, 5 is the second hole transport layer, 6 is the light emitting layer, 7 is the hole blocking layer, 8 is the electron transport layer, 9 is the electron injection layer, and 10 is the cathode layer. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials are available on the market unless otherwise specified, and the % in the following examples are all mass percentages unless otherwise specified.
[0045] Preparation Example
[0046] This preparation example provides the synthesis process of the compound involved in the present invention. The other compounds not involved in the following preparation examples can be obtained by those skilled in the art by referring to the following content.
[0047] Synthesis of intermediate 1:
[0048]
[0049] Synthesis of intermediate 1-2:
[0050] Under nitrogen protection, add intermediate 1-1 (100.0 g, 0.49 mol), 1,5-dibromo-2,4-difluoro-benzene (137.3 g, 0.50 mol), tetrakis(triphenylphosphine)palladium (2.9 g, 2.5 mmol), potassium carbonate (102.4 g, 0.74 mol), tetrabutylammonium bromide (3.2 g, 9.9 mmol), toluene (1 L), ethanol (400 mL), pure water (200 mL) to a three-necked flask, replace the reaction flask with nitrogen three times, and then heat it to 80 ° C and react for 8 hours. After the reaction solution is cooled to room temperature, it is washed with water until neutral, the organic phase is dried with anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 131.7 g of intermediate 1-2 with a yield of 76.2%.
[0051] Synthesis of intermediate 1-3:
[0052] Add intermediate 1-2 (130.0 g, 0.37 mol) and dichloromethane (1.5 L) to a dry three-necked flask, cool the reaction system to -5 to 0 ° C using an ice-salt bath, drop boron tribromide (373.1 g, 1.49 mol), stir at room temperature for 6 h, and then pour into ice water to quench the reaction. The organic phase is then washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column to obtain 102.2 g of intermediate 1-3 with a yield of 81.9%.
[0053] Synthesis of intermediate 1-4:
[0054] Add intermediate 1-3 (100.0 g, 0.30 mol), potassium carbonate (82.4 g, 0.60 mol), N,N-dimethylformamide (1 L) to a dry three-necked flask, and heat to 120°C for 4 h. After the reaction solution is cooled to room temperature, pour it into water under stirring to precipitate solids. After filtering, the filter cake is completely dissolved in toluene, and then washed with water until neutral. The organic phase is dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 69.1 g of intermediate 1-4 with a yield of 73.5%.
[0055] Synthesis of intermediate 1-5:
[0056] In a dry three-necked flask, add intermediate 1-4 (65.0 g, 0.21 mol), pinacol diboron (72.6 g, 0.25 mol), 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (1.5 g, 2.1 mmol), potassium acetate (40.5 g, 0.41 mol), toluene (800 mL), replace the reaction flask with nitrogen three times and heat it to reflux for 8 hours. After the reaction solution is cooled to room temperature, it is washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column to obtain 57.7 g of intermediate 1-5 with a yield of 77.3%.
[0057] Synthesis of intermediate 1-6:
[0058] Under nitrogen protection, add intermediate 1-5 (50.0g, 0.14mol), 4-bromo-1-iodo-2-methoxybenzene (44.1g, 0.14mol), tetrakis(triphenylphosphine)palladium (0.8g, 0.7mmol), potassium carbonate (38.1g, 0.28mol), tetrabutylammonium bromide (0.9g, 2.8mmol), toluene (600mL), ethanol (200mL), pure water (100mL) to a three-necked flask, replace the reaction flask with nitrogen three times, and then heat it to 80℃ for 8h. After the reaction solution is cooled to room temperature, it is washed with water until neutral, the organic phase is dried with anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 41.6g of intermediate 1-6 with a yield of 71.6%.
[0059] Synthesis of intermediate 1-7:
[0060] Add intermediate 1-7 (40.0 g, 95.0 mmol) and dichloromethane (800 mL) to a dry three-necked flask, cool the reaction system to -5 to 0°C using an ice-salt bath, drop boron tribromide (71.4 g, 0.28 mol), stir at room temperature for 6 h, and pour into ice water to quench the reaction. The organic phase is then washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by a silica gel column to obtain 56.8 g of intermediate 1-7 with a yield of 79.6%.
[0061] Synthesis of intermediate 1:
[0062] Add intermediate 1-7 (50.0 g, 0.12 mol), potassium carbonate (33.9 g, 0.24 mol), N,N-dimethylformamide (1 L) to a dry three-necked flask, and heat to 120°C for 4 h. After the reaction solution is cooled to room temperature, pour it into water under stirring to precipitate solids. After filtering, the filter cake is completely dissolved in toluene, and then washed with water until neutral. The organic phase is dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 39.8 g of intermediate 1 with a yield of 83.7%.
[0063] Intermediate 2 Synthesis:
[0064]
[0065] Synthesis of intermediate 2-1:
[0066] According to the synthesis method of intermediate 1-6, 4-bromo-1-iodo-2-methoxybenzene was replaced by 4-bromo-2-iodo-1-methoxybenzene, and the yield was 67.2%.
[0067] Synthesis of intermediate 2-2:
[0068] According to the synthesis method of intermediate 1-7, intermediate 1-6 was replaced by intermediate 2-1, and the yield was 81.1%.
[0069] Intermediate 2 Synthesis:
[0070] According to the synthesis method of intermediate 1, intermediate 1-7 was replaced by intermediate 2-2, and the yield was 75.9%.
[0071] Synthesis of intermediate 3:
[0072]
[0073] Synthesis of intermediate 3-1:
[0074] According to the synthesis method of intermediate 1-2, 1,5-dibromo-2,4-difluoro-benzene was replaced by 1-bromo-3-chloro-2,4-difluorobenzene, and the yield was 67.7%.
[0075] Synthesis of intermediate 3-2:
[0076] According to the synthesis method of intermediate 1-3, intermediate 1-2 was replaced by intermediate 3-1, and the yield was 79.7%.
[0077] Synthesis of intermediate 3-3:
[0078] According to the synthesis method of intermediate 1-4, intermediate 1-3 was replaced by intermediate 3-2, and the yield was 82.3%.
[0079] Synthesis of intermediate 3-4:
[0080] According to the synthesis method of intermediate 1-5, intermediate 1-4 was replaced by intermediate 3-3, and the yield was 65.9%.
[0081] Synthesis of intermediate 3-5:
[0082] According to the synthesis method of intermediate 1-6, 4-bromo-1-iodo-2-methoxybenzene was replaced by 4-bromo-2-iodo-1-methoxybenzene, and intermediate 1-5 was replaced by intermediate 3-4, with a yield of 73.6%.
[0083] Synthesis of intermediate 3-6:
[0084] According to the synthesis method of intermediate 1-7, intermediate 1-6 was replaced by intermediate 3-5, and the yield was 75.1%.
[0085] Synthesis of intermediate 3:
[0086] According to the synthesis method of intermediate 1, intermediate 1-7 was replaced by intermediate 3-6, and the yield was 72.8%.
[0087] Intermediate 4 Synthesis:
[0088]
[0089] Synthesis of intermediate 4-1:
[0090] According to the synthesis method of intermediate 3-5, 4-bromo-2-iodo-1-methoxybenzene was replaced by 4-bromo-1-iodo-2-methoxybenzene, and the yield was 69.5%.
[0091] Synthesis of intermediate 4-2:
[0092] According to the synthesis method of intermediate 3-6, intermediate 3-5 was replaced by intermediate 4-1, and the yield was 71.9%.
[0093] Intermediate 4 Synthesis:
[0094] According to the synthesis method of intermediate 3, intermediate 3-6 was replaced by intermediate 4-2, and the yield was 77.2%.
[0095] Synthesis of intermediate 5:
[0096]
[0097] Synthesis of intermediate 5-1:
[0098] According to the synthesis method of intermediate 3-5, 4-bromo-2-iodo-1-methoxybenzene was replaced by 4-bromo-2-iodo-1-thioanisole, and the yield was 73.5%.
[0099] Synthesis of intermediate 5-2:
[0100] According to the synthesis method of intermediate 3-6, intermediate 3-5 was replaced by intermediate 5-1, and the yield was 68.1%.
[0101] Synthesis of intermediate 5:
[0102] According to the synthesis method of intermediate 3, intermediate 3-6 was replaced by intermediate 5-2, and the yield was 71.2%.
[0103] Synthesis of intermediate 6:
[0104]
[0105] Synthesis of intermediate 6-1:
[0106] According to the synthesis method of intermediate 3-5, 4-bromo-2-iodo-1-methoxybenzene was replaced by 4-bromo-1-iodo-2-thioanisole.
[0107] Synthesis of intermediate 6-2:
[0108] According to the synthesis method of intermediate 3-6, intermediate 3-5 was replaced by intermediate 6-1, and the yield was 70.3%.
[0109] Synthesis of intermediate 6:
[0110] According to the synthesis method of intermediate 6, intermediate 3-6 was replaced by intermediate 6-2, and the yield was 73.9%.
[0111] Synthesis of intermediate 7:
[0112]
[0113] Synthesis of Intermediate 7-1: According to the synthesis method of Intermediate 1-2, 1,5-dibromo-2,4-difluorobenzene was replaced by 1-bromo-3-chloro-2-fluorobenzene, and the yield was 78.2%. Synthesis of Intermediate 7-2: According to the synthesis method of Intermediate 1-3, Intermediate 1-2 was replaced by Intermediate 7-1, and the yield was 80.5%. Synthesis of Intermediate 7-3: According to the synthesis method of Intermediate 1-4, Intermediate 1-3 was replaced by Intermediate 7-2, and the yield was 74.6%. Synthesis of Intermediate 7-4: According to the synthesis method of Intermediate 1-5, Intermediate 1-4 was replaced by Intermediate 7-3, and the yield was 69.5%. Synthesis of Intermediate 7-5: According to the synthesis method of Intermediate 1-6, 4-bromo-1-iodo-2-methoxybenzene was replaced by 4-bromo-2-iodo-benzoic acid methyl ester, and Intermediate 1-5 was replaced by Intermediate 7-4, and the yield was 72.4%.
[0114] Synthesis of intermediate 7-6:
[0115] Under nitrogen protection, add intermediate 7-5 (40.0 g, 92.7 mmol) and tetrahydrofuran (600 mL) to a three-necked flask, add methylmagnesium bromide (1.0 M in THF, 278.2 mL) dropwise under stirring at room temperature, and heat to 50°C for 3 h after the addition is complete. After the reaction solution is cooled to room temperature, add aqueous ammonium chloride to quench the reaction, adjust the pH to weak acidity, and then wash with water to neutrality. The organic phase is dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 25.5 g of intermediate 7-6 with a yield of 63.7%.
[0116] Synthesis of intermediate 7:
[0117] Under nitrogen protection, intermediate 7-6 (20.0 g, 46.4 mmol), methanesulfonic acid (8.9 g, 92.7 mmol), and toluene (300 mL) were added to a three-necked flask, and the temperature was raised to 110°C for reaction for 3 h. The reaction solution was cooled to room temperature and washed with water until neutral, the organic phase was dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 13.6 g of intermediate 7 with a yield of 71.2%.
[0118] Synthesis of Intermediate 8:
[0119]
[0120] Synthesis of intermediate 8-1: According to the synthesis method of intermediate 7-5, 4-bromo-2-iodo-benzoic acid methyl ester was replaced by 5-bromo-2-iodo-benzoic acid methyl ester, and the yield was 76.3%. Synthesis of intermediate 8-2: According to the synthesis method of intermediate 7-6, intermediate 7-5 was replaced by intermediate 8-1, and the yield was 66.8%. Synthesis of intermediate 8: According to the synthesis method of intermediate 7, intermediate 7-6 was replaced by intermediate 8-2, and the yield was 69.2%.
[0121] Synthesis of intermediate 9:
[0122]
[0123] Synthesis of Intermediate 9-1: According to the synthesis method of Intermediate 1-2, 1,5-dibromo-2,4-difluorobenzene was replaced by 1,4-dibromo-2,5-difluorobenzene, and the yield was 78.5%. Synthesis of Intermediate 9-2: According to the synthesis method of Intermediate 1-3, Intermediate 1-2 was replaced by Intermediate 9-1, and the yield was 82.2%. Synthesis of Intermediate 9-3: According to the synthesis method of Intermediate 1-4, Intermediate 1-3 was replaced by Intermediate 9-2, and the yield was 76.9%. Synthesis of Intermediate 9-4: According to the synthesis method of Intermediate 1-5, Intermediate 1-4 was replaced by Intermediate 9-3, and the yield was 72.7%. Synthesis of Intermediate 9-5: According to the synthesis method of Intermediate 1-6, Intermediate 1-5 was replaced by Intermediate 9-4, and the yield was 77.3%. Synthesis of Intermediate 9-6: According to the synthesis method of Intermediate 1-7, Intermediate 1-6 was replaced by Intermediate 9-5, and the yield was 83.6%. Synthesis of Intermediate 9: According to the synthesis method of Intermediate 1, Intermediate 1-7 was replaced by Intermediate 9-6, and the yield was 76.1%.
[0124] Synthesis of intermediate 10:
[0125]
[0126] Synthesis of Intermediate 10-1: According to the synthesis method of Intermediate 9-5, 4-bromo-1-iodo-2-anisole was replaced by 4-bromo-2-iodo-anisole, and the yield was 75.9%. Synthesis of Intermediate 10-2: According to the synthesis method of Intermediate 9-6, Intermediate 9-5 was replaced by Intermediate 10-1, and the yield was 78.2%. Synthesis of Intermediate 10: According to the synthesis method of Intermediate 9, Intermediate 9-6 was replaced by Intermediate 10-2, and the yield was 71.5%.
[0127] Synthesis of intermediate 11:
[0128]
[0129] Synthesis of intermediate 11-1: According to the synthesis method of intermediate 9-5, 4-bromo-1-iodo-2-anisole was replaced by 4-bromo-1-iodo-2-thioanisole, and the yield was 73.3%. Synthesis of intermediate 11-2: According to the synthesis method of intermediate 9-6, intermediate 9-5 was replaced by intermediate 11-1, and the yield was 68.6%. Synthesis of intermediate 11: According to the synthesis method of intermediate 9, intermediate 9-6 was replaced by intermediate 11-2, and the yield was 72.8%.
[0130] Compound synthesis
[0131] Synthesis of compound 25:
[0132]
[0133] Under nitrogen protection, intermediate 1 (10.0 g, 25.9 mmol), compound 25-1 (7.9 g, 25.9 mmol), tetrakis(triphenylphosphine)palladium (0.30 g, 0.26 mmol), potassium carbonate (7.2 g, 51.8 mmol), tetrabutylammonium bromide (0.84 g, 2.6 mmol), toluene (200 mL), ethanol (60 mL), pure water (30 mL) were added to a three-necked flask. The reaction flask was replaced with nitrogen three times and then heated to 80°C for 6 h. The reaction solution was cooled to room temperature and washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and recrystallized from toluene / ethanol (volume ratio of 2:1) to obtain 9.4 g of compound 25 for recrystallization purification with a yield of 63.7%.
[0134] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 568.1733 [M+H] + ;
[0135] C42H21O2D5 (%) calculated value: C, 88.87; H, 5.49; O, 5.64; found value: C, 88.92; H, 5.41; O, 5.67;
[0136] Synthesis of compound 27:
[0137]
[0138] According to the synthesis method of compound 25, the raw material compound 25-1 was replaced by compound 27-1, and the yield was 65.2%.
[0139] The mass spectrometry results of the obtained samples were: HR-MS (APCI): m / z 626.1597 [M+H] + ;
[0140] C46H11O2D15 (%) calculated value: C, 88.30; H, 6.58; O, 5.11; found value: C, 88.36; H, 6.51; O, 5.15;
[0141] Synthesis of compound 32:
[0142]
[0143] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 2, and compound 25-1 was replaced by compound 32-1, with a yield of 61.3%.
[0144] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 518.1628 [M+H] + ;
[0145] C38H11O2D9 (%) calculated value: C, 88.19; H, 5.62; O, 6.18; found value: C, 87.18; H, 5.64; O, 6.21;
[0146] Synthesis of compound 33:
[0147]
[0148] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 2, and compound 25-1 was replaced by compound 33-1, with a yield of 60.7%.
[0149] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 616.2195 [M+H] + ;
[0150] C46H21O2D5 (%) calculated value: C, 89.73; H, 5.07; O, 5.20; found value: C, 89.76; H, 5.02; O, 5.22;
[0151] Synthesis of compound 50:
[0152]
[0153] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 3, and compound 25-1 was replaced by compound 50-1, with a yield of 63.4%.
[0154] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 618.2253 [M+H] + ;
[0155] C46H19O2D7 (%) calculated value: C, 89.44; H, 5.38; O, 5.18; found value: C, 89.51; H, 5.25; O, 5.24;
[0156] Synthesis of compound 54:
[0157]
[0158] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 4, and compound 25-1 was replaced by compound 54-1, with a yield of 64.1%.
[0159] The results of mass spectrometry of the obtained samples are: HR-MS (APCI): m / z 618.2516 [M+H] + ;
[0160] C46H19O2D7 (%) calculated value: C, 89.43; H, 5.39; O, 5.18; found value: C, 89.47; H, 5.28; O, 5.25;
[0161] Synthesis of compound 56:
[0162]
[0163] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 5, and compound 25-1 was replaced by compound 56-1, with a yield of 67.2%.
[0164] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 662.2752 [M+H] + ;
[0165] C48H19O2SD9 (%) calculated value: C, 87.10; H, 5.64; O, 2.42; found value: C, 87.18; H, 5.52; O, 2.45;
[0166] Synthesis of compound 59:
[0167]
[0168] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 6, and compound 25-1 was replaced by compound 59-1, with a yield of 61.8%.
[0169] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 636.2276 [M+H] + ;
[0170] C46H21OSD7 (%) calculated value: C, 86.89; H, 5.55; O, 2.52; found value: C, 86.92; H, 5.42; O, 2.58; compound 105 synthesis:
[0171]
[0172] Under nitrogen protection, intermediate 7 (10.0 g, 24.3 mmol), compound 105-1 (4.5 g, 26.7 mmol), sodium tert-butoxide (7.5 g, 77.7 mmol), Pd2(dba)3 (0.22 g, 0.24 mmol), XantPhos (0.28 g, 0.48 mmol) and toluene (200 mL) were added to the reaction bottle in sequence, and heated under reflux for 8 h. After the reaction was completed, the system was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and purified by silica gel column. After the column liquid was concentrated, it was recrystallized with an appropriate amount of toluene / ethanol to obtain 9.6 g of compound 105 with a yield of 78.6%.
[0173] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 502.3138 [M+H] + ;
[0174] C37H27ON (%) calculated value: C, 88.57; H, 5.44; O, 3.19; N, 2.79; found value: C, 88.61; H, 5.38; O, 3.16; N, 2.84;
[0175] Synthesis of compound 107:
[0176]
[0177] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 8, and compound 105-1 was replaced by compound 107-1, with a yield of 69.5%.
[0178] The mass spectrometry results of the obtained samples were: HR-MS (APCI): m / z 654.1337 [M+H] + ;
[0179] C49H35ON (%) calculated value: C, 90.03; H, 5.38; O, 2.45; N, 2.14; found value: C, 90.05; H, 5.33; O, 2.44; N, 2.18;
[0180] Synthesis of compound 108:
[0181]
[0182] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 8, and compound 105-1 was replaced by compound 108-1, with a yield of 74.3%.
[0183] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 592.1652 [M+H] + ;
[0184] C43H29O2N (%) calculated value: C, 87.29; H, 4.93; O, 5.41; N, 2.37; found value: C, 87.34; H, 4.87; O, 5.45; N, 2.34;
[0185] Synthesis of compound 121:
[0186]
[0187] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 1, and compound 105-1 was replaced by compound 121-1, with a yield of 76.1%.
[0188] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 767.3291 [M+H] + ;
[0189] C56H34O2N2 (%) calculated value: C, 87.70; H, 4.48; O, 4.17; N, 3.65; found value: C, 87.76; H, 4.41; O, 4.14; N, 3.69;
[0190] Synthesis of compound 171:
[0191]
[0192] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 9, and compound 105-1 was replaced by compound 171-1, with a yield of 73.6%.
[0193] The results of mass spectrometry of the obtained samples are: HR-MS (APCI): m / z 482.1537 [M+H] + ;
[0194] C34H11O2ND8 (%) calculated value: C, 84.80; H, 5.64; O, 6.64; N, 2.91; found value: C, 84.72; H, 5.67; O, 6.62; N, 2.99;
[0195] Synthesis of compound 172:
[0196]
[0197] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 10, and compound 105-1 was replaced by compound 172-1, with a yield of 68.2%.
[0198] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 586.3123 [M+H] + ;
[0199] C42H35O2N (%) calculated value: C, 86.12; H, 6.03; O, 5.46; N, 2.39; found value: C, 86.16; H, 5.96; O, 5.41; N, 2.47;
[0200] Synthesis of compound 174:
[0201]
[0202] According to the synthesis method of compound 25, the raw material intermediate 1 was replaced by intermediate 10, and compound 25-1 was replaced by compound 174-1, with a yield of 62.9%.
[0203] The mass spectrometry results of the obtained samples were as follows: HR-MS (APCI): m / z 550.3162 [M+H] + ;
[0204] C40H23O2N (%) calculated value: C, 87.39; H, 4.24; O, 5.82; N, 2.55; found value: C, 87.42; H, 4.27; O, 5.77; N, 2.54;
[0205] Synthesis of compound 178:
[0206]
[0207] According to the synthesis method of compound 105, the raw material intermediate 7 was replaced by intermediate 11, and compound 1055-1 was replaced by compound 178-1, with a yield of 71.5%.
[0208] The results of mass spectrometry of the obtained sample are: HR-MS (APCI): m / z 498.2257 [M+H] + ;
[0209] C34H11ONSD8 (%) calculated value: C, 82.05; H, 5.48; O, 3.21; N, 2.81; found value: C, 82.03; H, 5.43; O, 3.24; N, 2.85;
[0210] The compounds disclosed in the present invention can all be prepared by referring to the above preparation methods.
[0211] Example 1
[0212] This embodiment provides compounds 25, 27, 32, 33, 50, 54, 56, 59, 105, 107, 108, 121, 171, 172, 174, 178 and existing light-emitting layer host materials BH1 and BD01, respectively. 1 Energy level and HOMO, LUMO simulation calculation. The calculation method uses B3LYP hybrid functional, basis set 6-31g (d, P), and the results are shown in Table 1.
[0213] Table 1, T 1 Energy level and HOMO, LUMO simulation results
[0214] Compound HOMO(eV) LUMO(eV) <![CDATA[T 1 (eV)]]> Compound 25 -5.089 -1.683 1.714 Compound 27 -5.071 -1.702 1.721 Compound 32 -5.049 -1.807 1.945 Compound 33 -5.103 -1.604 1.960 Compound 50 -5.107 -1.646 1.720 Compound 54 -5.106 -1.649 1.722 Compound 56 -5.161 -1.675 1.718 Compound 59 -5.149 -1.666 1.717 Compound 105 -4.769 -1.415 2.062 Compound 107 -4.949 -1.255 2.259 Compound 108 -4.864 -1.531 2.064 Compound 121 -4.928 -1.643 2.056 Compound 171 -5.120 -1.753 2.059 Compound 172 -5.209 -1.423 2.256 Compound 174 -5.005 -1.661 2.062 Compound 178 -5.032 -1.609 2.076 BH1 -5.152 -1.662 1.720 BD01 -4.630 -1.499 1.765
[0215] As shown in Table 1, compared with the comparative materials, the compounds disclosed in the present invention have more suitable HOMO / LUMO, and these compounds are suitable for use as the main material of the light-emitting layer or the light-emitting material. The present invention uses xanthene derivatives in OLED devices to effectively improve the luminous efficiency and service life of the device.
[0216] Example 2
[0217] This embodiment provides an organic electroluminescent device, the structure of which is as follows: Figure 1 As shown, it includes a substrate 1, an anode layer 2, a hole injection layer 3, a first hole transport layer 4, a second hole transport layer 5, a light emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9 and a cathode layer 10 which are stacked in sequence.
[0218] Among them, the material of the anode layer 2 is indium tin oxide (ITO) with a high work function, the material of the hole injection layer 3 is HAT-CN with a thickness of 5nm; the material of the first hole transport layer 4 is HT1 with a thickness of 60nm; the material of the second hole transport layer 5 is HT2 with a thickness of 15nm; the light-emitting layer 6 uses compound 25 as the main material and BD01 as the light-emitting material, with a doping mass ratio of 3% and a thickness of 20nm; the material of the hole blocking layer 7 is HB with a thickness of 10nm; the material of the electron transport layer 8 is ET-1 with a thickness of 30nm; the material of the electron injection layer 9 is Liq with a thickness of 2nm; the material of the cathode layer is Al with a thickness of 100nm.
[0219] The basic material structure used in each functional layer of the device is as follows:
[0220]
[0221] The specific preparation steps of the above organic electroluminescent device are as follows:
[0222] 1) Clean the ITO anode on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone, and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes;
[0223] 2) On the ITO anode layer, a hole injection layer material (HI)HATCN is deposited by vacuum evaporation with a thickness of 5 nm, which serves as a hole injection layer;
[0224] 3) Vacuum evaporation of a hole transport material HT1 with a thickness of 60 nm was performed on the hole injection layer, and this layer was used as the first hole transport layer;
[0225] 4) depositing a hole transport material HT2 on the first hole transport layer HT1 by vacuum evaporation with a thickness of 15 nm, and this layer serves as the second hole transport layer;
[0226] 5) On the second hole transport layer, a light-emitting layer was co-deposited by vacuum evaporation, using compound 25 as the main material and BD01 as the light-emitting material, with a doping mass ratio of 3% and a thickness of 20 nm;
[0227] 6) On the light-emitting layer, a hole blocking material HB is deposited by vacuum evaporation with a thickness of 10 nm, and this layer serves as a hole blocking layer;
[0228] 7) On the hole blocking layer, the electron transport material ET-1 is deposited by vacuum evaporation with a thickness of 30 nm, and this layer serves as the electron transport layer;
[0229] 8) On the electron transport layer, the electron injection material Liq is evaporated by vacuum evaporation with a thickness of 2 nm, and this layer serves as the electron injection layer;
[0230] 9) On the electron injection layer, cathode Al is deposited by vacuum evaporation with a thickness of 100 nm. This layer is used as a cathode conductive electrode.
[0231] The implementation process of device examples 2 to 24 is the same as that of device example 1, except that the main material of the light-emitting layer or the light-emitting material is replaced by other developed compounds instead of compound 25 and BD01.
[0232] Comparative Example 1
[0233] The same as device embodiment 1, except that BH1 is used as the main material of the light-emitting layer instead of compound 3.
[0234] The components of different devices prepared in device embodiments 1 to 24 and comparative example 1 of the present invention are shown in Table 2:
[0235] Table 2. Comparison of organic electroluminescent device components of various device embodiments
[0236]
[0237]
[0238] The cathode and anode of each group of organic electroluminescent devices were connected by a known driving circuit, and the voltage-efficiency-current density relationship of the OLED device was tested by a standard method using a Keithley 2400 power supply combined with a PR670 photometer; the life of the device was tested by a constant current method under the test condition of an initial brightness of 1000 cd / m 2 The time it takes for the brightness to decay to 90% of the initial brightness is the LT90 life of the device. The test results are shown in Table 3.
[0239] Table 3, Performance results of organic electroluminescent devices in each group
[0240]
[0241] As can be seen from Table 3, the compounds provided by the present invention are applied to OLED devices as the main material of the light-emitting layer, and have excellent performance. For example, the compound 54 in device embodiment 7 is used as the main material of blue light, and compared with BH1 in comparative example 1, the luminous efficiency and service life are significantly improved, the luminous efficiency is increased by 29.2%, and the device life is increased by 68%. The compounds provided by the present invention have excellent performance as light-emitting materials. For example, compared with the comparative material BD01, the compound 121 in device embodiment 18 has a device luminous efficiency of 20.5% and a device life of 31%. It can be seen that the compounds of the present invention are selected as the main material of the light-emitting layer or the light-emitting material, and compared with the existing materials applied to OLED light-emitting devices, the luminous efficiency and life performance of the device are greatly improved, and it has a good industrialization prospect.
[0242] The present invention obtains a compound of a specific structure by connecting a condensed ring aromatic group or a heteroaromatic group to a core skeleton of xanthenefuran, xanthenethiophene, or xanthenefluorene at a specific substitution position, and further deuterates the compound. The compound has a suitable frontier orbital energy level and good thermal stability. The series of compounds provided by the present invention exhibit excellent performance as a main material or a luminescent material of a light-emitting layer in an organic electroluminescent (OLED) device, and have a significant effect on improving the efficiency and life of the device.
[0243] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A compound, characterized in that Having a structure as shown in formula (I), wherein either X1 or X2 is selected from O, S or CR1R2, and the other is a single bond; L is selected from fused ring aromatic groups, amino derivatives, and heteroaromatic groups containing nitrogen, oxygen, sulfur, and boron atoms; Ar1 is selected from substituted or unsubstituted aryl groups having 6 to 30 carbon atoms; R1, R2 are methyl or phenyl; At least 0 hydrogen atoms are replaced by deuterium atoms.
2. The compound according to claim 1, characterized in that Either X1 or X2 is O, and the compound has a structure shown in any one of A1 to A6, 3. The compound according to claim 1, characterized in that Either X1 or X2 is S, and the compound has a structure shown in any one of B1 to B6, 4. The compound according to claim 1, characterized in that Either X1 or X2 is CR1R2, and the compound has a structure represented by any one of C1 to C6, 5. The compound according to claim 1, characterized in that The compound has a chemical structure shown in any one of compounds 1 to 209, Here, D indicates that a hydrogen atom is replaced by deuterium.
6. An organic electroluminescent device comprising a light-emitting layer, characterized in that: The light-emitting layer comprises the compound according to any one of claims 1 to 5.
7. The organic electroluminescent device according to claim 6, characterized in that: The compound serves as a host material or a light-emitting material.
8. Use of the compound according to any one of claims 1 to 5 in an organic electroluminescent device.
9. An organic electroluminescent display device, characterized in that: An organic electroluminescent device comprising any one of claims 6 to 7.
10. Use of the organic electroluminescent device according to any one of claims 6 to 7 in an organic electroluminescent display device.
Citation Information
Cited By
Compound for organic luminescent material
CN119462592A
A compound for organic light-emitting material
CN119462592B
